2021
DOI: 10.1186/s12939-020-01353-7
|View full text |Cite
|
Sign up to set email alerts
|

Achieving equitable uptake of handwashing and sanitation by addressing both supply and demand-based constraints: findings from a randomized controlled trial in rural Bangladesh

Abstract: Background Supply driven programs that are not closely connected to community demand and demand-driven programs that fail to ensure supply both risk worsening inequity. Understanding patterns of uptake of behaviors among the poorest under ideal experimental conditions, such as those of an efficacy trial, can help identify strategies that could be strengthened in routine programmatic conditions for more equitable uptake. WASH Benefits Bangladesh was a randomized controlled efficacy trial that pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Nutrient-rich foods, which are essential for preventing anaemia, may be more accessible to wealthier households, thereby reducing the risk of developing anaemia [ 59 ]. Additionally, wealthier households may have superior sanitation infrastructure, which can help reduce infectious disease rates associated with anaemia [ 60 , 61 ]. Furthermore, wealth can also affect access to healthcare, including preventative measures and treatment for anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient-rich foods, which are essential for preventing anaemia, may be more accessible to wealthier households, thereby reducing the risk of developing anaemia [ 59 ]. Additionally, wealthier households may have superior sanitation infrastructure, which can help reduce infectious disease rates associated with anaemia [ 60 , 61 ]. Furthermore, wealth can also affect access to healthcare, including preventative measures and treatment for anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that implementing WASH that does not generate inequalities would require a tailored approach 29 . Members of our team have previously assessed equity in the WASH Benefits Bangladesh interventions with respect to measures of adherence 30 and others have assessed barriers and inequalities in effective WASH practices in the African setting 24 , 31 . These previous studies have demonstrated improved equity in WASH practices and this present analysis demonstrates that those improvements in equity carry forward to improvements in equity in child diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…However, adapting these evidence-based interventions to facilitate implementation at-scale in ways that maintain originally demonstrated levels of effectiveness has proved challenging (1-3). These challenges have been attributed in part to poor ability to adapt to context and retain effectiveness as interventions are implemented at scale (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%